A scoping review of crisis teams managing dementia in older people - Streater, Amy; Coleston-Shields, Donna Maria; Yates, Jennifer; Stanyon, Miriam; Orrell, Martin (Dove Medical Press, 2017)
Background: Research on crisis teams for older adults with dementia is limited. This scoping review aimed to 1) conduct a systematic literature review reporting on the effectiveness of crisis interventions for older people with dementia and 2) conduct a scoping survey with dementia crisis teams mapping services across England to understand operational procedures and identify what is currently occurring in practice. Methods: For the systematic literature review, included studies were graded using the Critical Appraisal Skills Programme checklist. For the scoping survey, Trusts across England were contacted and relevant services were identified that work with people with dementia experiencing a mental health crisis. Results: The systematic literature review demonstrated limited evidence in support of crisis teams reducing the rate of hospital admissions, and despite the increase in number of studies, methodological limitations remain. For the scoping review, only half (51.8%) of the teams had a care pathway to manage crises and the primary need for referral was behavioral or psychological factors. Conclusion: Evidence in the literature for the effectiveness of crisis teams for older adults with dementia remains limited. Being mainly cohort designs can make it difficult to evaluate the effectiveness of the intervention. In practice, it appears that the pathway for care managing crisis for people with dementia varies widely across services in England. There was a wide range of names given to the provision of teams managing crisis for people with dementia, which may reflect the differences in the setup and procedures of the service. To provide evidence on crisis intervention teams, a comprehensive protocol is required to deliver a standardized care pathway and measurable intervention as part of a large-scale evaluation of effectiveness.